Ventral striatum and amygdala activity as convergence sites for early adversity and conduct disorder - Holz, Nathalie E.; Boecker-Schlier, Regina; Buchmann, Arlette; Blomeyer, Dorothea; Jennen-Steinmetz, Christine; Baumeister, Sarah; Plichta, Michael M.; Schmidt, Martin H.; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Social cognitive and affective neuroscience, 2017)
Abstract. Childhood family adversity (CFA) increases the risk for conduct disorder (CD) and has been associated with alterations in regions of affective proces